10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
OBJECTIVE: Progression independent of relapse activity is a major determinant of long-term disability in multiple sclerosis, but its immunopathologic basis remains incompletely understood. We investigated whether relapse-independent progression in radiologically stable relapsing-remitting multiple sclerosis is associated with distinct cerebrospinal fluid inflammatory profiles and whether cytokine-network features provide information beyond single-mediator levels. METHODS: In this prospective observational cohort study, baseline cerebrospinal fluid cytokine and chemokine profiling was performed in 346 RRMS patients, 61 primary progressive multiple sclerosis (PPMS) patients, and 196 neurological controls without inflammatory or neurodegenerative central nervous system disease. After 2-year clinical and MRI follow-up, 37 RRMS patients with clinical relapse and/or MRI activity were excluded, leaving 309 relapse-free and MRI-stable RRMS patients classified as stable RRMS (n = 241) or RRMS with PIRMA (n = 68). Cytokines were analyzed using two-part hurdle models, cytokine interactomes, and machine-learning classifiers. RESULTS: Quantitative cytokine analyses distinguished multiple sclerosis from controls but showed substantial overlap across multiple sclerosis phenotypes. RRMS with PIRMA showed higher cerebrospinal fluid levels of tumor necrosis factor-α, interleukin-17, and RANTES than stable RRMS. Network analyses showed a more integrated cytokine interactome in RRMS with PIRMA. The network-level model best distinguished RRMS with PIRMA from stable RRMS, with an area under the curve of 0.86, sensitivity of 77%, and specificity of 76%. INTERPRETATION: Relapse-independent progression in multiple sclerosis is associated with selective cytokine changes and broader reorganization of inflammatory network architecture, supporting cerebrospinal fluid cytokine interactome profiling as a translational approach to immune stratification.